LITTERING AND ENVIRONMENTAL NEGLIGENCE ASIA A BIBLIOMETRIC ANALYSIS OF GLOBAL RESEARCH TRENDS (2000–2025) - Yahaya, Nurul Faezah; Yahaya, Mohd Firdaus; Ishak, Mariyah; Mohamed Indera Alim Sah, Nor Athirah; Idris, Mohammad Ihsan; Md Yusnan, Mohammad Baihaqi; Ahmad, Nadzrah (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This bibliometric analysis investigates global research trends on littering and environmental negligence in Asia over a 25-year period, from 2000 to 2025. The study aims to explore the development of scholarly attention in this field, identify major thematic areas, and assess the role of technology, tools, and education in shaping the academic discourse. Despite the growing urgency of waste-related environmental issues in the region, systematic evaluations of the academic response remain limited. To address this gap, data were extracted from the Scopus database using a structured search strategy focused on the keywords "technology", "tools", and "education". After applying inclusion criteria based on language, document type, and publication year, a total of 986 articles were selected for analysis. The dataset was processed and refined using Scopus Analyzer, OpenRefine, and VOSviewer software, enabling detailed mapping of publication trends, co-authorship networks, subject area distribution, and keyword co-occurrence. Results show a significant increase in publication output from 2015 onwards, with peak activity observed between 2021 and 2025. Most contributions came from the disciplines of environmental science, agricultural and biological sciences, and earth and planetary sciences, with limited representation from social sciences, behavioural research, and policy studies. Southeast Asian countries, particularly Indonesia, Malaysia, and Thailand, were among the top contributors, though varying in levels of international collaboration. Keyword analysis revealed dominant themes related to ecological impact, marine litter, and decomposition, with emerging interest in microplastics and environmental education. This study contributes to a deeper understanding of the research landscape on environmental negligence in Asia and highlights the need for more interdisciplinary engagement. The findings offer direction for future studies and policy development aimed at advancing sustainable waste management practices through integrated scientific and educational approaches.